2003
DOI: 10.1051/forest:2003008
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the interaction between climate, soil and leaf area index in a Quercus ilex ecosystem

Abstract: -In Mediterranean-type ecosystems, water availability is one of the most significant variables that regulates whole plant leaf area. An equilibrium should exist between climate, soil and leaf area in such water-limited conditions. The aim of this study was to identify the relations between leaf area index (LAI), environment (climate, soil) and fluxes (water, carbon) in Mediterranean evergreen oak (Quercus ilex L.) ecosystems. To achieve this objective, 50-years simulations were performed using the FOREST-BGC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 64 publications
4
50
0
2
Order By: Relevance
“…Because leaf surfaces are the primary sites of energy, gas and water exchanges and of important physiological processes such as photosynthesis, interception, transpiration, and evapotranspiration are a function of LAI. Hoff & Rambal (2003) have also indicated that with increasing LAI, drainage decreases while transpiration and interception increases. Therefore, the relatively high soil moisture content at 1200 m elevation might have been due to the lower LAI.…”
Section: Soil Physical and Chemical Propertiesmentioning
confidence: 98%
“…Because leaf surfaces are the primary sites of energy, gas and water exchanges and of important physiological processes such as photosynthesis, interception, transpiration, and evapotranspiration are a function of LAI. Hoff & Rambal (2003) have also indicated that with increasing LAI, drainage decreases while transpiration and interception increases. Therefore, the relatively high soil moisture content at 1200 m elevation might have been due to the lower LAI.…”
Section: Soil Physical and Chemical Propertiesmentioning
confidence: 98%
“…The functioning of Quercus ilex stands in the south of France was simulated by Hoff et al (2002) and Hoff and Rambal (2003) using the Forest-BGC model. C use rules in this simple model are implemented so as to follow an optimal trajectory: trees use C first into leaves and fine roots for maximizing productivity, while minimizing water limitation; finally, stems appear as an end product built with the remaining C. Other modeling exercises with Q. ilex ecosystems also retained water-related constraints for their C use rules.…”
Section: S Rambal Et Al: Drought and C Partitioningmentioning
confidence: 99%
“…Sin embargo, en el presente estudio solo se encontraron diferencias morfológicas sin relación significativa con las ambientales. Por lo tanto, las diferencias ambientales no parecen estar afectando a las características morfométricas de la misma manera en todos los sitios (Hoff & Rambal, 2003). Debido a la cercanía y origen común de las subpoblaciones de Q. germana, las diferencias morfológicas no deberían presentarse aun en ambientes distintos.…”
Section: Análisis De La Relación Morfológica Y Ambientalunclassified
“…However, in this study, only morphological differences without significant relation to the environmental ones were found. Therefore, the environmental differences do not seem to affect the morphometric characteristics in the same manner in all locations (Hoff & Rambal, 2003). Due to the closeness and common origin of the sub-populations of Q. germana, the morphological differences should not be present even in different environments.…”
Section: Analysis Of the Morphological And Environmental Relationmentioning
confidence: 99%